TRANSLATION OF ENGLISH IMPERATIVE SENTENCES IN PROCEDURAL TEXTS INTO INDONESIAN - Ludji, Ifoni (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 21 (2014): September 2014, 2014)
This study aims at exploring the types of English imperative sentences in procedural text and analyzing the reason why such translation procedures are applied. The method in conducting this study was descriptive qualitative method. The researcher did observation by taking notes and also applied the document analysis. The result of the study indicates that the types of English imperative sentences used in English procedural texts and their Indonesian translation in psychology book entitled “What I Wish I Knew at Eighteen” commonly use three types of imperative such as negative commands, requests, and positive commands. In addition, four kinds of translation procedures are used in this study. The existences of translation procedures become the reason of why such translation procedures are being applied and also there are three basic reason namely, semantic factor, syntactic factor and culture factor.
Keywords: procedural text, imperative sentences, translation procedures